Dominating Sets and Connectivity Preservation in Power Graphs of Symmetric and Cyclic Groups - Ika Metiza Maris; Rawdah Adawiyah Tarmizi; Nor Hafizah Md Husin (Program Studi Matematika - Fakultas Matematika dan Ilmu Pengetahuan Alam Universitas San Pedro, 2026)
The power graph P(G) is a simple graph associated with a group G that represents power relations among its elements. Although power graphs have been widely studied in connection with domination and connectivity, the effect of removing dominating sets, particularly those excluding the identity element, on graph connectivity has not been examined in detail. This study aims to characterize dominating sets in power graphs of finite groups and to investigate whether connectivity is preserved after their removal, with emphasis on symmetric groups and cyclic groups. This research employs a theoretical and analytical approach based on group theory and algebraic graph theory. The results show that, for symmetric groups Sn, there exists a dominating set excluding the identity element such that the power graph remains connected after its removal. Furthermore, for cyclic groups Cn, any generator forms a minimum dominating set, and the power graph remains connected after its removal.